The level of knowledge and behaviours-related health lifestyle as risk factors for cardiovascular disease in the adult population - Bartoszek, Adrian; Korniszuk, Maria Jolanta; Dec, Izabela (Journal of Education, Health and Sport, 2017)
Introduction and purpose: Cardiovascular diseases (CVDs) are the biggest threat to the health of the population in Poland and are the most important cause of mortality. Most of the cardiovascular risk factors is located in the area of health behaviours related to lifestyle. The aim of the study was to assess the level of knowledge and analysis of selected health behaviours as risk factors for cardiovascular disease in the adult population Material and methods: The study involved 170 people age adults living in the Lublin province Podkarpackie and in the period from November 2013 to March 2014. The research method was a diagnostic survey and research tool questionnaire. Results: Cardiovascular disease occurred in 58% of subjects. The level of knowledge of respondents on the risk factors of cardiovascular disease is high. Declared health behaviour in terms of cigarettes not in the majority: smokes cigarettes daily 12%, up to 84% of consumed alcohol, a subjective evaluation on the excess amount of salt refers to 42%. BMI depends on gender, age, education and place of residence. Excessive salt intake is related to the unsatisfactory financial situation. On active smoking significantly affected by gender and education on alcohol abuse and the most accepted variables. Conclusions: The level of knowledge of the subjects on the risk factors of cardiovascular disease is high. The main CVD risk factors in the study group is the consumption of alcohol in excessive amounts Cardiovascular risk factors significantly influenced by age, gender, place of residence, education, financial situation and family.